PESANTREN DAN PENGEMBANGAN PENDIDIKAN PERDAMAIAN Studi Kasus di Pesantren An-Nidzomiyyah Labuan Pandeglang Banten - Muslihah, Eneng (Universitas Islam Negeri Raden Intan Lampung, 2014)
THE PESANTREN (BOARDING SCHOOL) AND THE ISLAMIC EDUCATION FOR PEACE DEVELOPMENT: A Case Study in An-Nidzomiyyah Islamic School at Labuan, Pandeglang,Banten: This study attempts to review the pattern of Islamic peace education and its influence on the de-radicalization of terrorism. The study was conducted at the Islamic boarding school of An- Nidzomiyah at Labuan, Pandeglang, Banten. Data were collected through questionnaires distributed to a number of 70 respondents whom were selected and assigned randomly. The study finds out: First, the rate of Islamic peace education level reached 85% while the rate of de-radicalization of terrorism reaches 81%, which shows the high category and satisfying. Secondly, there is a positive and significant effect of de-radicalization of terrorism program as indicated by a score of 20.40%. The rest is affected by other factors that are still to be investigated. Third, the higher level of the Islamic peace education achievement, the higher de- radicalization of terrorism level will be.